The economics of cancer care. Issue 12 (13th November 2007) - Costantini, Massimo; Beccaro, Monica
Abstract : N Bosanquet & K Sikora. Cambridge. Published by Cambridge University Press, 2006, 130.00 (hardback), pp 185. ISBN-13 978-0-85007-0. ISBN-10 0-521-85007-X.